Removal of endosulfan from water by municipal waste incineration fly ash-based geopolymers: Adsorption kinetics, isotherms, and thermodynamics - Luttah, Isaac; Onunga, Daniel O.; Shikuku, Victor O.; Otieno, Benton; Kowenje, Chrispin O. (Frontiers in Environmental Chemistry, 2023)
Alkali-activated municipal waste incinerator-fly ash (MWFA) based geopolymers (GPA, GPB, and GPC) were synthesized under different sodium silicate to sodium hydroxide (SS/SH) ratios. The geopolymers were applied in the removal of endosulfan a persistent and toxic chemical, from water. The adsorbents were characterized by XRD, SEM-EDX, and FTIR. Variation of SS/SH ratios resulted in morphologically distinguishable geopolymers with different compositions. The adsorption equilibrium data were best described by Langmuir isotherm. The maximum adsorption capacities increased with an increase in SS/SH ratios in the order 2.29, 33.95, 38.44, and 41.93 mg/g for MWFA, GPA, GPB, and GPC, respectively. The kinetic data were best described by the pseudo-first-order model wherein the adsorption rate ("k" _"1" ) was independent of the SS/SH ratio and the geopolymer composition. The thermodynamic parameters, that is enthalpy (∆H > 0), Gibbs free energy (∆G < 0), entropy (∆S > 0), and activation energy (Ea > 0) show that the processes were endothermic, spontaneous, physical (Ea and ∆H < 40 kJ/mol) and entropy-driven. Alkalination was beneficial since the geopolymers had a higher adsorption capacity (~8-10 times) and affinity for endosulfan (~30 times) than the precursor material (MWFA). The adsorption mechanism entailed electrostatic interactions and hydrogen bonding. The MWFA-based geopolymers are, therefore, potential alternative low-cost adsorbents for the removal of endosulfan from water and a strategy for the valorization of MWFA.